The Influence of Digital Leadership on Employee Performance through Work Engagement - Eny Rochmatulaili; Erik Bisri Alamsyah; Muhammad Alif Rahman (Feedforward: Journal of Human Resource, 2026)
This study examines the influence of digital leadership on employee performance, with a particular emphasis on the mediating role of work engagement. In the context of rapid digital transformation, organizational effectiveness is increasingly shaped not only by technological advancement but also by the readiness of human resources and leadership capabilities in managing digital change. A quantitative research approach was employed using a survey method involving N=150 employees working in organizations undergoing digital transformation. Data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that digital leadership has a significant positive effect on work engagement, which in turn enhances employee performance. Furthermore, mediation analysis confirms that work engagement plays a significant mediating role in the relationship between digital leadership and employee performance. Theoretically, this study extends the Job Demands–Resources (JD-R) framework by incorporating digital leadership as a critical job resource in the digital era. Practically, the findings provide important implications for organizations in designing leadership development strategies that foster employee engagement and improve performance outcomes in digitally transforming environments.